Generation of Patient-Derived Podocytes from Skin Biopsies - Rose, Victoria; Müller-Deile, Janina (Journal of Visualized Experiments, 2023)
Podocytes are epithelial cells sitting on the urinary site of the glomerular filtration barrier that contribute to the selective filter function of the glomerulus. Mutations in podocyte-specific genes can cause focal segmental glomerulosclerosis (FSGS), and podocytes are also affected in many other primary and secondary nephropathies. Due to their differentiated nature, primary cell culture models are limited for podocytes. Therefore, commonly conditionally immortalized cells are used. However, these conditionally immortalized podocytes (ciPodocytes) have several limitations: the cells can dedifferentiate in culture, especially when they reach confluency, and several podocyte-specific markers are either only slightly or not expressed at all. This brings the use of ciPodocytes and their applicability for physiological, pathophysiological, and clinical reach into question. Here, we describe a protocol for the generation of human podocytes-including patient-specific podocytes-from a skin punch biopsy by episomal reprogramming of dermal fibroblasts into hiPSCs and subsequent differentiation into podocytes. These podocytes resemble in vivo podocytes much better in terms of morphological characteristics, like the development of foot processes and the expression of the podocyte-specific marker. Finally, yet importantly, these cells maintain patients' mutations, resulting in an improved ex vivo model to study podocyte diseases and potential therapeutic substances in an individualized approach.
CRIS-Team Scopus Importer:2023-06-30